Polymorphic cobalt sulfide-embedded graphene foam with ultralong cycling and ultrafast rate capability for potassium-ion batteries - Ye, Xinli (2023)
Potassium-ion batteries (KIBs) attract growing attention due to their low price and abundant resources. However, the main drawback is the large-sized potassium ions, which results in a lack of superior capacity and desirable stable materials. We herein propose the Co9S8/GF nanocomposite synthesized by a solvothermal route followed by heat treatment under the reduction atmosphere with the CoS/GF nanocomposite as the control group. The as-synthesized Co9S8 has a typical morphology of vertically arranged uniform nanosheet arrays. The Co9S8/GF nanocomposite electrode delivers a capacity of 345.65 mAh·g-1 after 600 cycles at 500 mA·g-1 and even 343.06 mAh·g-1 after 1360 cycles at 5000 mA·g-1 in KIBs. Besides, the discharge capacity can reach 461.05 mAh·g-1 after the current increases to 5000 mA·g-1 and a reversible capacity of 578.40 mAh·g-1 when the current density recovers to 250 mA·g-1 again. At last, the charge storage behaviors are mainly discussed, and the unique structure can suffer the volumetric change, especially at high current density, which opens up a novel and effective way to build the embedded porous structure for the next-generation KIB technology.